Sputum culture contamination and associated characteristics in a diagnostic clinical trial, Papua New Guinea - ND. Tenakanai; J.K. Banamu; Y. Lin; D. Walsh; R. Simbil; M. Globan; A. Penn-Nicholson; P. du Cros; J. Greig (The Union, 2024)
SETTING: Papua New Guinea is a high-burden multidrug-resistant TB (MDR/RR-TB) country that reports low rates of bacteriological confirmation. Sputum drug susceptibility testing for second-line drugs is important. Access to culture is limited. OBJECTIVE: To evaluate the prevalence of mycobacterial sputum sample culture contamination and determine factors associated with contamination. DESIGN: A retrospective analysis of data from a TB diagnostic accuracy study that used culture as the diagnostic reference standard. Data included characteristics of people with presumptive pulmonary TB who provided sputum, sputum quality and culture results. RESULTS: Sputum (1-3 samples) was collected from 174 adults. The median age was 33 years (IQR 24-47). Of 337 samples sent for culture, 28% were contaminated. Contamination was strongly associated with samples self-collected by participants outside clinic hours (aOR 5.69; 95% CI 2.62-12.38). Contamination risk increased with delays in shipping to the reference laboratory (aOR 1.19 per day, 95% CI 1.10-1.29) beyond the minimum 3 days. Contamination was less frequent among people aged 35-44 years compared to 18-24 years (aOR 0.27, 95% CI 0.10-0.73). Sputum quality was not associated with culture contamination. CONCLUSION: Culture contamination could be reduced using spot sputum collection, expedited submission to laboratories and faster shipping when required.